Three-minute all-out test in swimming - Tsai, M.-C.; Thomas, S. G. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To validate the 3-minute all-out exercise test (3MT) protocol against the traditional critical-speed (CS) model (CSM) in front-crawl swimming.